2010
DOI: 10.4103/1817-1745.66661
|View full text |Cite
|
Sign up to set email alerts
|

Possible causes of seizure after spine surgery

Abstract: Seizure after laminectomy for spinal procedure is very rare and has not been reported after lipomyelomeningocele surgery beforehand. Here, two cases of seizure following laminectomy for lipomyelomeningocele are reported. The exact etiology of the event is unknown but anesthetic material, pneumocephalus, intracranial hypotension subsequent to cerebrospinal fluid leakage after spinal procedures, spinal-induced seizure and the potential toxic effect of fat molecules could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This fact may indicate that seizures are not caused by elevations in ICP. On the other hand, some reports have concluded that intracranial hypotension subsequent to cerebrospinal fluid (CSF) leakage could be a cause of seizure [10] , [11] . In addition, Agrawal et al reported a patient suffering from frequent postural seizures [12] : seizures occurred only when sitting up, and resolved when lying down.…”
Section: Discussionmentioning
confidence: 99%
“…This fact may indicate that seizures are not caused by elevations in ICP. On the other hand, some reports have concluded that intracranial hypotension subsequent to cerebrospinal fluid (CSF) leakage could be a cause of seizure [10] , [11] . In addition, Agrawal et al reported a patient suffering from frequent postural seizures [12] : seizures occurred only when sitting up, and resolved when lying down.…”
Section: Discussionmentioning
confidence: 99%
“…The possible causes of generalised seizures may be multifactorial such as pneumocephalus, subdural haemorrhage following cerebrospinal fluid (CSF) leak, epilepsy disorder, post-meningitis, cerebrovascular disease, hyponatremia or allergy to contrast medium. [ 1 2 3 ] All metabolic causes and above-mentioned factors were ruled out. Although CSF leak is usually benign, the associated intracranial hypotension can result in complications such as subdural haemorrhage and seizures.…”
mentioning
confidence: 99%